2015
DOI: 10.1080/14459795.2015.1020959
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of ‘losses disguised as wins’ and near-misses in a slot machine game

Abstract: Individually, both near-misses and losses disguised as wins (LDWs) have been seen to exert pro-motivational effects on gambling. However, it is not clear whether both structural characteristics are effective within the same game. Participants (n ¼ 40) played a slot machine simulation. The simulation delivered near-misses, wins and 'fullmisses'. Half the participants also received LDWs that occurred independently of the outcomes on the payline. Valence and motivation ratings were collected after each round. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Additionally, individuals appear to overestimate their number of wins by miscategorizing LDWs as real wins (Jensen et al, 2013). Accordingly, individuals reportedly enjoy LDW games more than non-LDW games (Sharman et al, 2015). Extending these previous findings, the results of the present study show that in an ecologically valid setting, LDWs are associated with more persistent within-session gambling behaviour compared to losses, but less persistent gambling behaviour compared to real wins.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Additionally, individuals appear to overestimate their number of wins by miscategorizing LDWs as real wins (Jensen et al, 2013). Accordingly, individuals reportedly enjoy LDW games more than non-LDW games (Sharman et al, 2015). Extending these previous findings, the results of the present study show that in an ecologically valid setting, LDWs are associated with more persistent within-session gambling behaviour compared to losses, but less persistent gambling behaviour compared to real wins.…”
Section: Discussionsupporting
confidence: 72%
“…This may accordingly play a potential etiological role in the development of gambling problems. Given that LDW games are associated with reinforcing celebratory events, elicit physiological reactions (Dixon et al, 2010), influence gambling-related cognitions (Jensen et al, 2013) and are attractive to gamblers (Sharman et al, 2015), LDWs might increase within-session game persistence and consequently, the risk of more intense gambling behaviour, at least among novice gamblers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sounds can be used to influence game preference (Dixon et al, 2014), but it has also been found that sounds can effectively be used unmask the disguised losses (Dixon et al, 2015a). Sharman, Aitken, and Clark (2015) studied the impact of near misses where half of the subjects were exposed to near misses that were also combined with LDWs. Valence and motivation ratings were collected after each round.…”
Section: Reinforcement Without Winningmentioning
confidence: 99%
“…However, the reel patterns on the basic slot machine used in these studies are generally easy to discriminate which makes the generalization account less likely. If the patterns were more difficult to discern from one another, or the win and near-miss stimuli were partitioned from other reel patterns by common outcomes [18] -as in the case of losses being disguised as wins [19] -then the generalization account would be more plausible. Furthermore, one would expect that as a person gains more experience playing a machine, they would become better at making discriminations between win and loss reel patterns.…”
Section: Near Misses As Global and Local Eventsmentioning
confidence: 99%